Ethical implications of neurotechnology in industry-academia partnerships: Insights from patient and research participant interviews - Meredith V. Parsons; Maya Skolnik; Judith Mwobobia; Erin D. Solomon; James M. DuBois; Tristan McIntosh (PLoS ONE, 2025)
Background Neurotechnologies often advance through industry-academia (IA) partnerships and offer insight into brain and nervous system functions, bringing improved diagnosis and treatment options to patients. Both neurotechnology and IA partnerships pose ethical challenges that can impact research participation experiences, patient treatment, and health outcomes. Methods Investigators conducted interviews with 16 patients who used neurotechnology devices in therapeutic or research settings. Interviews explored participants’ experiences using neurotechnology, perspectives on IA partnerships, preferences for neural data use and long-term care, and advice for future neurotechnology device users. Data were analyzed using inductive thematic analysis. Results Participants were generally supportive of IA partnerships. However, they also recognized that these relationships could unduly influence research and clinical decisions. While participants appreciated the information shared with them prior to using the neurotechnology, informational gaps were still identified regarding the impact of devices on daily living, disclosure of relationships with industry, plans for data use and sharing, and plans for long-term care and upkeep of the device. Participants generally supported neural data sharing to advance research or improve patient care, although for some this depended on data sensitivity and how privacy would be protected. Participants advocated for post-trial access to experimental neurotechnologies and felt that responsibility for long-term care and device maintenance is best shared among companies, doctors, academic researchers, insurance companies, and patients themselves. Future device users were advised to self-advocate, maintain realistic expectations, and learn about a device before engaging with it. Conclusion Given current and future capabilities of neurotechnologies and the data they generate, IA partnerships that develop and commercialize neurotechnologies require careful consideration and implementation of practices that meaningfully consider patient perspectives, needs, and safety. Such practices include bias management in the design, conduct, and reporting of neurotechnology research, neural data sharing and use, post-trial device access, and informed consent processes.